A comparison between active and passive communities of Ostracoda (Crustacea) in a tropical temporary lake. (4th May 2021) - Rosa, Jonathan; Golec, Cláudia; Bonecker, Claudia C.; Martens, Koen; Higuti, Janet
ABSTRACT: Some microcrustaceans living in temporary waterbodies produce drought-resistant stages under adverse conditions. These structures accumulate in the sediment, forming an egg bank in which eggs can remain viable for many years. Here, we evaluate the contribution of ostracod resting eggs to the structure of the active ostracod community in a tropical temporary lake located in the Upper Paraná River floodplain, Brazil. The active ostracod communities were sampled by hand net, while sediment samples (egg banks) were collected using a core sampler. Sediments were oven-dried, then re-hydrated with filtered lake water and kept in hatching chambers. A total of 13 ostracod species were recorded, eight species in the passive community, and nine species in the active community, four species were recorded in both communities. The species composition between active and passive communities was significantly different. Five species of the active community could be of allochthonous origin and are most likely introduced by flooding or by other dispersal vectors. In conclusion, the egg bank adds species not necessarily found in the active community, thus acting in the maintenance and enrichment of the local and regional faunas.